LEGAL IMPLICATIONS OF CONSUMER PROTECTION DISPUTES ON CASH DELIVERY SYSTEMS IN E-COMMERCE - Cokorda Anom Baruna Kiswara; I Made Dedy Priyanto (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2023)
This article aims to verify the validity of online purchases and transactions between sellers and buyers through the Cash Delivery System and the legal impact of breach of contract or failure to comply. The methods used in this article are legal research methods employing legal, conceptual, and case-by-case approaches. Based on the research results, online sales contracts will be effective if they meet the four conditions specified in the Criminal Code, in accordance with Law No. 19 of 2016 on Changes to Law No. 11 of 2008 on Electronic Information and Transactions. Therefore, online sales agreements are as robust as other sales contracts. This is a legal application when a buyer makes transactions online through an E-Commerce application under Law Number 19 of 2016 concerning Changes to Law Number 11 of 2008. Electronic products are not clearly and elaborately regulated. According to criminal law, buyers are obliged to compensate for losses, transfer risks, support legal costs, and enter into contracts with the parties concerned.